Digital Skills in Igniting Accounting Undergraduates’ Entrepreneurship Intention - Mohamad Fazil, Nadiah Farhanah; Ahmad, Noor Lela; Yusof, Rohaila (International Business Education Journal, 2022)
The purpose of this study is to study the impact of digital skills in developing entrepreneurship intention. Three dimensions of digital skills are studied which are technical digital skills, cognitive digital skills and social-emotional digital skills. An online survey was conducted among 52 Accounting undergraduates in a local university. Correlation and regression analysis was conducted in SPSS to study the impact between the variables. The results show that technical digital skills and social-emotional digital skills have a positive and significant impact on Accounting undergraduates’ entrepreneurship intention. Meanwhile, cognitive digital skills do not impact Accounting undergraduates’ entrepreneurship intention.